Osteogenic potential of different chalcones in an in vivo model: A preliminary study - Mezadri, Telmo José; Ortolan, Xana Raquel (Journal of Oral Research, 2019)
To evaluate the osteogenic potential of chalcones using the rat critical size calvarial defect. Methods. The chalcones were synthesized from acetophenone following the Claisen-Schmidt aldol condensation method by varying the substituted benzaldehydes (3,4-Cl; 4-Cl; 4-CH3; 4-OCH3, H). The five chalcone molecules were evaluated in three concentrations (1%, 5% and 10%) in comparison to control and vehicle (Vaseline) groups. The results of the remaining wound areas were calculated statistically by the ANOVA method followed by the Student-Newman-Keuls test and the histological sections were analyzed qualitatively by light microscopy. Results. All molecules at 10% concentration showed significant bone closure compared to the control, vehicle and chalcone groups at 1% concentration (p<0.01). Active osteoblasts were observed on the repair surfaces in all groups treated with chalcones. Treatment with the C5 molecule at concentration of a 10% resulted in greater bone neoformation compared to the other molecules, with features of secondary bone observed.